Emotions in Transmigration - Brooks, A. author. aut Link
XII, 207 p.
Keywords: The book explores the intersection of emotions and migration in a number of case studies from across the USA, Europe and Southeast Asia, including the transmigration of female domestic workers, transmigrant marriages, transmigrant workers in the entertainment industry and asylum seekers and refugees who are the victims of domestic violence.